Outcome Comparison of Endovascular and Open Surgery for the Treatment of Acute Superior Mesenteric Artery Embolism: A Retrospective Study - Li, Wenrui; Cao, Saisai; Zhang, Zhiwen; Zhu, Renming; Chen, Xueming; Liu, Bin; Feng, Hai (Frontiers in Surgery, 2022)
Background: Few centers have adopted endovascular therapy for the treatment of superior mesenteric artery embolism (SAME). We sought to evaluate the effect of endovascular therapy on outcomes for the treatment of SAME and identify the posttreatment prognostic factors. Methods: A single-center, retrospective cohort review was performed on all consecutive SAME patients presenting between 2013 and 2021. Patients with mesenteric artery thrombosis, mesenteric venous thrombosis, nonocclusive mesenteric ischemia, ischemia associated with aortic dissection and who had only conservative treatment were excluded. Demographic factors and preoperative metabolic status were compared. Results: Forty-one consecutive patients were identified with SAME (median age, [range]35-86 years). Endovascular therapy was initiated in 14 patients with no clinical evidence of bowel necrosis, with mainly mechanical thrombectomy, and technical success was achieved in 93%. Endovascular therapy had advantages in duration surgery time, blood loss, bowel rest time, ICU time and ventilator use. There was no difference in bowel necrosis, length of necrotic bowel resected or in-hospital mortality between the two groups. An initial WBC count >15* 103/dL and neutrophil count >13* 103/dL were associated with an increased risk of bowel necrosis, and an initial white blood cell count, renal function, American Society of Anesthesiologists (ASA>3) and necrotic bowel >2 meters were associated with increased mortality. Conclusions: Endovascular therapy has altered the management of SAME, and it may be adopted in selected patients who are not at risk for bowel necrosis. Avoidance of bowel necrosis patients and close monitoring for bowel necrosis is important.